2016
DOI: 10.1055/s-0036-1593619
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in the Younger Patient

Abstract: The rate of total knee arthroplasty (TKA) utilization in younger patients (< 65 years old) is increasing. Little is known regarding demographics and in-hospital outcomes in this population. The National Hospital Discharge Survey (NHDS) database was searched using International Classification of Diseases, Ninth Revision (ICD-9) procedure codes for patients admitted to U.S. hospitals for unilateral primary TKA between 2001 and 2010. Patients were separated into young (< 65 years of age) and senior cohorts (≥ 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…Shah et al. (2017) found a significantly higher occurrence of obesity and morbid obesity among patients <65.We could not show that increased weight was associated with increased risk of revision in younger patients, but patients weighing 60–69 kg had a lower risk of revision. These results may be due to the lower number of patients aged 18–55 years.…”
Section: Discussioncontrasting
confidence: 64%
“…Shah et al. (2017) found a significantly higher occurrence of obesity and morbid obesity among patients <65.We could not show that increased weight was associated with increased risk of revision in younger patients, but patients weighing 60–69 kg had a lower risk of revision. These results may be due to the lower number of patients aged 18–55 years.…”
Section: Discussioncontrasting
confidence: 64%
“…In three studies, the mortality rate in patients ≥ 80 years of age was higher than that in the control groups [ 48 , 59 , 60 ]. In another study, the mortality rate in patients ≥ 65 years of age was higher than that in patients < 65 years of age [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the impact of age on patient satisfaction is still debated even though the incidence of TKA uptake among younger (< 55 years) and geriatric (> 80 years) patients is increasing [ 18 , 20 ]. Some studies have shown good treatment results for TKA even when performed at extreme ages.…”
Section: Introductionmentioning
confidence: 99%
“…2015, Shah et al. 2017). The number of patients currently living with a TKA suggests a large potential revision healthcare burden (Hamilton et al.…”
Section: Discussionmentioning
confidence: 99%